2020
DOI: 10.3390/plants9030395
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Foliar Functional Traits of S. pyrenaicus subsp. carpetanus under the Ongoing Climate Change: A Retrospective Survey

Abstract: The sensitivity of stomatal behavior and patterning (i.e., distribution, density, size) to environmental stimuli, renders them crucial for defining the physiological performance of leaves. Thus, assessing long-term modifications in stomatal traits in conserved specimens arises as a valuable eco-physiological approach to predict how the rising trend of warmer, drier summers could affect plant fitness; particularly in mountain areas already experiencing climate aggravation and lacking the related monitoring sche… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 46 publications
1
3
0
Order By: Relevance
“…The summer drought has implied a generalised decrease in SLA CWM across the gradient, a result that we expected to find and that is consistent with the results of previous research where a decrease in SLA is observed in dry months (Garnier et al, 2001;Rossatto et al, 2013) or over several decades of increased aridity Magaña Ugarte et al, 2020). The decrease in SLA in our study is mainly due to an increase in leaf weight that may come from two distinct but complementary acclimation processes: some shrubs lose part of their leaves before the summer drought (Simões et al, 2008) and could be expected to lose the leaves less adapted to summer conditions (intracohort selection), that is those with higher SLA.…”
Section: Discussionsupporting
confidence: 92%
“…The summer drought has implied a generalised decrease in SLA CWM across the gradient, a result that we expected to find and that is consistent with the results of previous research where a decrease in SLA is observed in dry months (Garnier et al, 2001;Rossatto et al, 2013) or over several decades of increased aridity Magaña Ugarte et al, 2020). The decrease in SLA in our study is mainly due to an increase in leaf weight that may come from two distinct but complementary acclimation processes: some shrubs lose part of their leaves before the summer drought (Simões et al, 2008) and could be expected to lose the leaves less adapted to summer conditions (intracohort selection), that is those with higher SLA.…”
Section: Discussionsupporting
confidence: 92%
“…The suggested robustness in S. carpetanus may be linked to long-term feedbacks driven by long-standing environmental coarsening in this mountain range. These feedbacks may have caused the selection of functional traits that confer greater drought endurance, such as smaller leaf areas to reduce the ratio of hydraulic demand to supply (Magaña Ugarte et al, 2020). In F. curvifolia, the inferred robustness could be attributed to its strong competitiveness for resources and dominance in these xerophytic pastures (Pescador et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, and akin to the findings by Buchner et al [12] in Senecio incanus, our results in S. carpetanus and F. curvifolia indicate the xanthophyll cycle operates in response to the daily thermal and light intensity variations in these species, rather than in response to year-to-year climate wavering (Figures 2 and 3). The latter is associated with superior life strategies and functional trait differentiation in S. carpetanus and F. curvifolia, resulting from the selection over time of functional traits granting greater tolerance to the coarsening climate in this mountain range and the firm competitiveness and dominance in these xerophytic pastures, respectively [28,44].…”
Section: Discussionmentioning
confidence: 99%
“…The occurrence and the severity of summer stress underline the more challenging conditions constraining plant life in Mediterranean high-mountains [2,27]. Furthermore, the marked interannual climate variability characteristic of these habitats, coupled with the higher frequency and severity of combined drought and heat episodes witnessed in recent years [28,29], adds further pressures to the establishment and survival of Mediterranean high-mountain plants [30,31].…”
Section: Introductionmentioning
confidence: 99%